Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises - Page 112: 42



Work Step by Step

Simplify $\sqrt{-18}$ to obtain: $=\sqrt{9(-1)(2)} \\=\sqrt{3^2(-1)(2)} \\=3\sqrt{(-1)(2)}$ Since $\sqrt{-1} = i$, the expression above simplifies to: $=3i\sqrt{2}$ Thus, the given expression is equivalent to: $=\dfrac{-9-3i\sqrt{2}}{3}$ Divide each term of the numerator by the denominator to obtain: $=\dfrac{-9}{3} - \dfrac{3i\sqrt{2}}{3} \\=\color{blue}{-3-i\sqrt{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.